Arterialized collateral capillaries progress from nonreactive to capable of increasing perfusion in an ischemic arteriolar tree. (11th April 2018) - Gouin, Kenneth H.; Hellstrom, Sara K.; Clegg, Lindsay E.; Cutts, Josh; Mac Gabhann, Feilim; Cardinal, Trevor R.
Abstract: Objective: CCA, outward remodeling of capillaries that anastomose 2 arteriolar trees with different parent feed arteries, may represent a therapeutic target for patients who lack collaterals. ACCs can reperfuse an ischemic tree, but their functional capacity is unknown. Therefore, we determined whether ACCs mature into resistance vessels that regulate blood flow following arterial occlusion. Methods: We ligated the lateral spinotrapezius feed artery in Balb/C mice, which induces CCA. At days 7 and 21 following occlusion, we measured vasodilation of ACCs using intravital microscopy and blood flow in the ischemic tree using LSF. We determined the presence of ACCs and neurovascular alignment with immunofluorescence. Results: At day 7, ACCs do not vasodilate following muscle contraction and have reduced responses to endothelial‐ and smooth muscle‐dependent agents. By day 21, ACCs exhibit normal vasodilation, accompanied by normalized increases in relative blood flow to the ischemic zone. Although functioning as resistance vessels by regulating blood flow, ACCs do not appear to be innervated. Conclusions: ACCs mature into resistance vessels that regulate blood flow to the downstream tissue. Therefore, induction of mature ACCs may be a target for reducing ischemia in patients who lack collateral networks.